ChemInform Abstract: Stereoselective Synthesis of Lignans of Three Structural Types from a Common Intermediate, Enantioselective Synthesis of (+)‐Yangambin. Issue 9 (March 2015) - Syed, Majid Khalil; Murray, Cian; Casey, Mike
Abstract The enantioselective synthesis of yangambin (I) is described.